All that is mine I carry with me : a novel [large type] - Landay, William (Thorndike Press large print mystery series., 2023)
"One afternoon in 1975, ten-year-old Miranda Larkin comes home from school to find her mother missing. So begins a mystery that will span a lifetime. What happened to Jane Larkin? Investigators suspect Jane's husband, but no evidence is found linking him to a crime, and the case fades from the public's memory. Jane's three children are left to be raised by the man who may have murdered their mother. Two decades later, the remains of Jane Larkin are found. The investigation in awakened. The children, now grown, are forced to choose sides. With their father or against him? Guilty or innocent? And what happens if they are wrong?"--